Thermochemical characterization of cassava peel biocoke for renewable energy at varying pyrolysis temperatures - Asri, Gani; Erdiwansyah, .; Desvita, Hera; Rizalman, Mamat; Mohd Fairusham, Ghazali; Ichwansyah, Fiqih; Ahmad, Naim (Elsevier B.V., 2025)
The growing global energy demand and the need for sustainable alternatives have driven the exploration of biomass waste as a renewable energy source. Cassava peel, an abundant agro-industrial residue, holds potential as a feedstock for solid biofuel production through thermochemical processes. This study aims to investigate the physicochemical transformation of cassava peel into biocoke via low-temperature torrefaction and to evaluate its suitability for energy and environmental applications. Torrefaction was conducted at 150 ◦C, 160 ◦C, 170 ◦C, 180 ◦C, and 190 ◦C. Analytical techniques were employed, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDS), calorimetry, and lignocellulosic composition analysis. FTIR revealed dominant OH, aliphatic C–H, and C–O functional groups, with aromatic and triple-bond structures appearing above 170 ◦C. SEM analysis showed significant porosity development and surface fragmentation at 180–190 ◦C. EDS confirmed carbon and oxygen as major elements, while K, Ca, Cl, and Mg were consistently present, and P, S, and Si emerged at 190 ◦C. The calorific value increased with temperature, peaking at 15.31 MJ/kg at 170 ◦C. This study is novel in providing a comprehensive, temperaturedependent characterization of cassava peel biocoke, integrating surface chemistry, mineral exposure, and energy content. Unlike previous studies focusing only on proximate analysis, this work links structural changes with functional reactivity. In conclusion, cassava peel demonstrates strong potential as a low-cost, hemicellulose-rich biomass for producing porous and moderately energetic biocoke under mild thermal conditions, suitable for combustion, adsorption, and environmental applications.